Triangulated Pigmentocracy - Nsiangani, Kibavuidi (USK Journal of Health & Psychology, 2024)
This article re-examines colorism, reframing it from a passive "cultural preference" to a measurable, intentional socio-clinical byproduct of colonial political engineering. The core hypothesis posits a strategy called Colonial Triangulation: an external power imposes a hierarchy and fosters internal competition for proximity to the imposed ideal, leading to a self-reproducing system termed Triangulated Pigmentocracy. The work proposes a Mechanistic Model detailing the psychological factors driving this system: Narcissism (predicting status worship), Machiavellianism (predicting administrative sorting), Psychopathy (predicting neglect), and Sadism (predicting degradation). The primary contribution is a "clinically sharp conceptual framework" and a falsifiable research program anchored in African epistemic sovereignty, yielding testable predictions about discourse, markets (e.g., skin-lightening), and politics (e.g., identity wars). This shifts the focus to colorism as a structural political-economic tool sustaining colonial power.
Colonial Dark-Tetrad Dynamics Behind Colorism, Ethnicization, and Diaspora Fragmentation
Keywords: Triangulated Pigmentocracy; Coloniality; Colorism; Dark Tetrad; Narcissism; Machiavellianism; Psychopathy; Sadism; African Epistemology; Ethnicization; Diaspora Fragmentation; Skin Lightening; Toxic Cosmetics; Minamata Convention; Governance Technology; Structural Adjustment; Decolonial Clinical Practice.